Development in Venezuela of Energy System Based in the Hydrogen. Part III: Transport and Distribution - Posso, Fausto (Rev. Téc. Fac. Ing. Univ. Zulia)
The aim of this work is to develop and evaluate a mathematical model for the process of transport and distribution of hydrogen for use as an energetic vector in rural sectors of Venezuela. Pressurized containers of 50 l of geometric volume and 200 bars of pressure transported by truck was the way chosen as the most appropriate means of transport. The non-linear model has been used to calculate the transport and distribution costs, depending on the number of rural homes to be supplied. The results show that economy of scale means the overall cost can be reduced as the number of homes served and/or distance travelled increases. Finally, we see that investment costs are the largest portion of the overall cost, whereas in terms of the operating costs, it is the cost of the lorry that is the main item.